2013
DOI: 10.1590/s2238-10312013000400003
|View full text |Cite
|
Sign up to set email alerts
|

Suitability of Brazilian ports to international standards of port needs: a case study in the port of Salvador

Abstract: The objective of this paper is to identify what requirements must meet Brazilian ports to suit the demands of the international market. To meet this goal the study discusses the evolution of the law from port modernization of ports and port participation in the Brazilian transportation system. It also discusses the major theories of international trade and theories of competitive strategies, utilizing the contributions of Adam Smith, David Ricardo, Michael Porter and Klaus Esser. The study makes a comparative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 4 publications
0
1
0
4
Order By: Relevance
“…Brazilian port governance some studies can be found in the body of the literature. Barros and Barros (2013) affirmed that the low modal integration and port infrastructure deficit hinders the advanced stage of the Brazilian ports. Galvão et al (2013Galvão et al ( , 2017 stated that in Brazil, the 1993 Ports Act had its effects and policy changes regarding the Government's strategic sectors during the 1990s and early 2000s.…”
Section: Mabrmentioning
confidence: 95%
“…Brazilian port governance some studies can be found in the body of the literature. Barros and Barros (2013) affirmed that the low modal integration and port infrastructure deficit hinders the advanced stage of the Brazilian ports. Galvão et al (2013Galvão et al ( , 2017 stated that in Brazil, the 1993 Ports Act had its effects and policy changes regarding the Government's strategic sectors during the 1990s and early 2000s.…”
Section: Mabrmentioning
confidence: 95%
“…A estruturação de um sistema portuário eficiente e eficaz é um fator fundamental para o desenvolvimento econômico de um País. Além de o transporte marítimo ser considerado o mais barato e versátil, os portos também promovem uma integração entre este tipo e os demais modos de transporte BARROS, 2013). Em seu relatório de 2017 sobre o transporte marítimo, a Conferência das Nações Unidas para o Comércio e Desenvolvimento indicou que o total de volumes transportados pela via marítima no mundo foi de 10,3 bilhões de toneladas em 2016, estimando-se um crescimento 2,8% em 2017, alcançando-se um total de 10,6 bilhões de toneladas transportadas (UNCTAD, 2017, p. 10).…”
Section: Portos Infraestrutura Pública E Serviço Públicounclassified
“…De acordo com Barros e Barros (2013) o setor portuário lida anualmente com cerca de 700 milhões de toneladas de mercadorias diversas e é responsável por mais de 90% das exportações, destacando o papel estratégico que o sistema portuário deve a economia. Em 2007, os portos foram responsáveis pelo manuseio de 76,7% do comércio internacional brasileiro, totalizando um valor de US $ 188 bilhões em transações de mercadorias.…”
Section: Introductionunclassified
“…Em 2007, os portos foram responsáveis pelo manuseio de 76,7% do comércio internacional brasileiro, totalizando um valor de US $ 188 bilhões em transações de mercadorias. Em 2010, o volume transportado por mar representou 96% das exportações e 88% das importações (BARROS;BARROS, 2013). Em 1993, foi promulgada a Lei 8.630, denominada de Lei de Modernização dos Portos, que atribui à União o direito de explorar o porto organizado, diretamente ou mediante concessão sempre precedida de licitação.…”
Section: Introductionunclassified
See 1 more Smart Citation